2020
DOI: 10.1124/jpet.120.000179
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Immunogenicity Is Negatively Correlated with Anti-Hinge Antibody Levels in Patients with Rheumatoid Arthritis

Abstract: Patients with rheumatoid arthritis (RA) are frequently treated with anti-TNF immunoglobulin therapy but develop neutralizing antibodies against these drugs, necessitating therapeutic monitoring of drug concentrations and anti-drug antibodies. Patients with RA have multiple factors related to their autoimmune disposition that interfere with conventionally used methods to detect anti-drug antibodies. Currently deployed analytical methods have significant limitations that hinder clinical interpretation and/or ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This technology has the potential to be applied in combination as a pre-treatment to a number of immunogenic biologics in which ADA responses can limit therapeutic efficacy. Examples of immunogenic therapeutics with efficacy-limiting ADA responses include chronically administered monoclonal antibody therapies such as adalimumab, 63 enzyme replacement therapies such as phenylalanine ammonia lyase for the treatment of phenylketonuria, 64 and factor VIII replacement for hemophilia A. 65 With further validation, it may be used in combination with adeno-associated viral vectors to prevent ADAs and allow re-dosing.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has the potential to be applied in combination as a pre-treatment to a number of immunogenic biologics in which ADA responses can limit therapeutic efficacy. Examples of immunogenic therapeutics with efficacy-limiting ADA responses include chronically administered monoclonal antibody therapies such as adalimumab, 63 enzyme replacement therapies such as phenylalanine ammonia lyase for the treatment of phenylketonuria, 64 and factor VIII replacement for hemophilia A. 65 With further validation, it may be used in combination with adeno-associated viral vectors to prevent ADAs and allow re-dosing.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has the potential to be applied in combination as a pretreatment to a number of immunogenic biologics in which ADA responses can limit therapeutic efficacy. Examples of potential use cases include preventing ADAs to chronically administered monoclonal antibody therapies such as adalimumab 62 , enzyme replacement therapies such as phenylalanine ammonia lyase for the treatment of phenylketonuria 63 and factor VIII replacement for hemophilia A 64 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating ADAs and adalimumab it was shown that at least 98% had speci c ADAs against adalimumab with a neutralizing effect at 2 weeks after the start of drug initiation (22). However, it has been seen that anti-hinge antibodies had less neutralization of adalimumab (23). In one study, it was shown that patients with high levels of anti-adalimumab antibodies had increased Rheumatoid Factor values and positive association with increased C-Reactive Protein and DAS28 (24).…”
Section: Discussionmentioning
confidence: 99%